Content Mixes used in Advertisement on Social Media for Particular Categories of Product (Global Journal of Management and Business Research, 2016)
Innovativeness is requirement for a long ran we can#x2019;t overlook the significance of either. This research work talks about that which where the major categories of products and services being advertised on social media during the period of this study. This further suggests with regards to the identification of the content which has been used to advertise the selected categories of products/services identified for the study on the selected social media website. Further the sixteen identified variables which are Message, Tag line, Brand Logo, Images, Celebrity, Offers/Discounts, Colour, Text, Customer Reviews, Jingles, Audio, Video, Product Information, Product Comparison, Price information, Call To Action and there relation with the selected social media websites and categories of products and services selected for the research study has been studied in detail